Golden ratio-based leverage targeting and the ESG performance of US and European listed firms - Csapi, Vivien; Ulbert, József; Tóth-Pajor, Ákos (PTE KTK Műhelytanulmányok, 2023)
Our paper aims to assess whether golden ratio-based leverage targeting is linked to better ESG performance. To answer this research question, we study how ESG performance affects the distance between the leverage targets and the levels defined by the golden ratio and examine the temporal dynamics of leverage in relation to the distance between leverage targets and the golden ratio levels. Our main findings show that when firms in the European manufacturing sector have better ESG performance, they choose to have leverage targets closer to the levels defined by the golden ratio. In this case, firms adjust their book leverage considering the distance between the leverage targets and the golden ratio levels. Our results highlight that prudential sustainability reporting regulation and higher ESG exposure can guide firms toward a more harmonized capital structure.